(3GdGOGQI GdMOjKI hGdfXe GdGdcJQhfjI (B/s - (3LGSe, eLjOs ((3GdGScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2005)
(3JWhQ eQGMd GdUfGYI YHQ GdYUhQ h Yde GdGOGQI h GQJHGWg HGdUfGYI GdMOjKI h GdfXe GdGdcJQhfjI GdMOjKI h GOGQI GdYedjGJ GdUfGYjI GdMOjKI(B, (3GVGaI Gdi JUeje h JaYjd YedjGJ GdGfJGL h eaghe LOjO dfXGe GdGfJGL HGdfXe GdGdcJQhfjI GdMOjKI h OQGSI GdhbJ h cPG GdefJL eLGd GdGcJTGa h GdHMK(B, (3cPdc GdJNWjW GdGSJQGJjLj ddeUfY GdGdcJQhfj haj GdGNjQ SjGSGJ GdGfJGL ddeUfY GdGdcJQhfj(B.s
Keywords: (3GdGOGQI GdMOjKIs; (3GdfXe GdGdcJQhfjIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s